The Influence of Self-Control, Cyberslacking, and Academic Stress on the Academic Performance of Graduate Students - Satrio Ahmadtul Firdaus Romadhoni; Arief Noviarakhman Zagladi (Universitas Negeri Padang, 2024)
This research explores how self-control, cyberslacking, and academic stress affect the academic performance of graduate students at the State University of Malang. A quantitative methodology using multiple linear regression was applied to analyze the relationships between these variables. Data were collected through a questionnaire based on a Likert scale, with a sample of 55 respondents chosen using proportional random sampling. The findings indicate that, on an individual basis, self-control did not significantly affect academic achievement, whereas both cyberslacking and academic stress do have a considerable impact. Collectively, these three variables explain 68.7% of the variance in academic performance, as indicated by the Adjusted R Square value. The study concludes that cyberslacking and academic stress are critical factors influencing students' academic success. Therefore, implementing strategies for stress management and reducing cyberslacking activities are essential for enhancing academic outcomes. Additionally, fostering self-control can help students better navigate the effects of these other variables.